2009
DOI: 10.2355/isijinternational.49.261
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Current Gas Metal Arc Welding under Different Shielding and Pulse Parameters; Part 2: Behaviour of Metal Transfer

Abstract: The behaviour of metal transfer and arc stiffness understood in terms of arc pressure (P a ) of pulsed current gas metal arc welding (P-GMAW) using mild steel filler wire have been studied with respect to change in pulse parameters under different gas shieldings of Arϩ2%CO 2 and Arϩ18%CO 2 . The arc environment revealing the droplet transfer from electrode to weld pool in bead on plate weld deposition has been studied by high speed video graphy. Effect of pulse parameters has been considered by their hypotheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It is found that a low arc voltage of about 24 V creates instability in shielding jacket due to relatively low arc pressure. 21) However, during pulse off period (Fig. 13) the disturbance in arc profile has been found comparatively more than that of the pulse on time.…”
Section: Under Arϩ2%co 2 Gas Shieldingmentioning
confidence: 98%
See 4 more Smart Citations
“…It is found that a low arc voltage of about 24 V creates instability in shielding jacket due to relatively low arc pressure. 21) However, during pulse off period (Fig. 13) the disturbance in arc profile has been found comparatively more than that of the pulse on time.…”
Section: Under Arϩ2%co 2 Gas Shieldingmentioning
confidence: 98%
“…The interruption of arc profile and shielding in P-GMAW process at an appropriate gas flow rate largely depends upon degree of fluctuation in arc pressure at different arc stiffness and arc length. The arc length and stiffness primarily varies as a function of f, I m and arc voltage [11][12][13]21) whereas the degree of fluctuation of arc pressure significantly depends upon the ratio of (I b /I p ) as observed earlier. 11,12) The fluctuation in arcing due to large variation of I b and I p causing low I b /I p ratio may create instability in shielding gas jacket resulting into formation of vortex at the boundary of arc profile.…”
Section: Stability In Arc Shieldingmentioning
confidence: 99%
See 3 more Smart Citations